Mineralocorticoid Receptor Antagonists in Diabetic Kidney Disease - Nina Vodošek Hojs; Sebastjan Bevc; Robert Ekart; Nejc Piko; Tadej Petreski; Radovan Hojs (MDPI AG, 2021)
Diabetes mellitus is a global health issue and main cause of chronic kidney disease. Both diseases are also linked through high cardiovascular morbidity and mortality. Diabetic kidney disease (DKD) is present in up to 40% of diabetic patients; therefore, prevention and treatment of DKD are of utmost importance. Much research has been dedicated to the optimization of DKD treatment. In the last few years, mineralocorticoid receptor antagonists (MRA) have experienced a renaissance in this field with the development of non-steroidal MRA. Steroidal MRA have known cardiorenal benefits, but their use is limited by side effects, especially hyperkalemia. Non-steroidal MRA still block the damaging effects of mineralocorticoid receptor overactivation (extracellular fluid volume expansion, inflammation, fibrosis), but with fewer side effects (hormonal, hyperkalemia) than steroidal MRA. This review article summarizes the current knowledge and newer research conducted on MRA in DKD.